Decreased sensitivity to loss of options in patients with Parkinson's disease. (9th September 2022) - Shigemune, Yayoi; Kawasaki, Iori; Baba, Toru; Takeda, Atsushi; Abe, Nobuhito
Abstract: Humans prefer to have many options when making decisions. When there is a threat of options disappearing, humans invest more to keep these options available, indicating that they are sensitive to the loss of options. This study examined whether patients with Parkinson's disease (PD), a disease characterized by dopamine depletion, try to keep options available when options are disappearing. Twenty-seven PD patients without dementia and 27 healthy controls (HCs) performed the door game, in which participants were presented with multiple alternatives in the form of three doors, each associated with a different point distribution. The participants were asked to maximize their point earnings by finding the best door. The task included two conditions. In the shutter condition, shutters gradually closed on doors that were not chosen; once the shutters completely closed, the door was no longer available. There were no shutters in the control condition. The results revealed that the HCs switched doors more often in the shutter condition than in the control condition, indicating a tendency to keep options available. However, the PD patients did not show such differences between the two conditions. The difference in the number of switches between the shutter and control conditions in the PD patients was significantly positively correlated with the distribution of dopamine transporters in the left striatum, as measured by 123 I-ioflupane-SPECT (DaTSCAN) images. These results suggest that PD patients are less sensitive to the loss of options, and this decreased sensitivity may be caused by a decline in dopaminergic neurotransmission. Highlights: Humans want to keep options available, even if the process is costly. PD patients did not show a tendency to keep options available. Reduced sensitivity to the loss of options was related to striatal dopamine levels.